Exploring the Drivers of Undergraduates’ Perceived Usefulness and Intention to Adopt Cloud Computing: A Study in Chengdu, China - Yang, Xing (Scholar: Human Sciences, 2025)
Purpose: This paper investigates the elements that affect the perceived usefulness and intention to use cloud computing among undergraduates in Chengdu, China. Seven latent variables were specifically chosen, which were perceived ease of use, subjective norms, perceived usefulness, attitude, perceived cost of usage, perceived security, and intention to use. Research Design, Data, and Methodology: The researcher employed quantitative research methodologies and delivered 500 questionnaires to undergraduates at the target universities who were enrolled in four key majors. This survey made use of the multistage sampling approach. The associations between the variables under investigation were ascertained using the structural equation model (SEM) and confirmatory factor analysis (CFA). The examination of the research data validated all the conjectures, revealing that the technology’s perceived usefulness was the key motivator for university students to interact with cloud computing. Results: The results indicated important references for curriculum design and promotion strategies in cloud computing education in universities, as well as empirical evidence for education administrators and policymakers to formulate more effective educational technology policies, encouraging the incorporation and assimilation of cloud computing technologies within academic environments, thereby enhancing its accessibility and utilization. Conclusions: The findings revealed that perceived usefulness exerted the greatest pronounced influence on the dependent variable, affecting the decision to employ cloud computing.